Sports marketing strategy and its relationship to the competitive advantage of institutional clubs in Iraq - Ali Rashid; Thamer Rija (التربية الرياضية)
The research aimed to identify the correlation between the sports marketing strategy and the competitive advantage of institutional sports clubs in Iraq. The researchers used the descriptive approach using the analytical survey method and correlational relationships, in order to suit the requirements and procedures of his research. For the purpose of achieving the objectives of any research and studying its variables, it is necessary to know the original society with its characteristics and components. Because the use of any method is considered an incomplete case unless the study population is described clearly and accurately. The research population was determined from members of the administrative bodies of institutional sports clubs in Iraq, who numbered (404) members of the administrative body, distributed among (49) sports clubs, and a sample was determined. Search from the origin community by a percentage of(86.63). Since the research sample was approved as (350) members of the administrative body out of the total number, the questionnaires were distributed to the application sample, which numbered (150) members of the administrative body in the institutional clubs on 3/28/2022, and the phrases were arranged randomly so that the respondent would not be limited to one area. One particular over the other. Then the questionnaires were collected after a specific period, and they were rearranged in an organized manner according to each field in preparation for subjecting them to statistical treatments. The researchers used the SPSS statistical package, through a set of statistics that suit the requirements of the research and methods for obtaining the required results. The results of the sample proved Application: There is a moral correlation to the results of the significance level values ​​between the two research measures (sports marketing strategy) and (competitive advantage). The researcher attributes this to the moral correlation in the variables being that competitive advantage requires successful management that believes in organizational change to develop a sports marketing strategy that will be a center for achieving imports. The additional level is under specialized marketing management, and all the results of the three measurement areas have been discussed in detail.